First Quantitative Imaging of Organic Fluorine within Angiogenic Tissues by Particle Induced Gamma-Ray Emission (PIGE) Analysis: First PIGE Organic Fluorine Imaging - Gérard Déléris; Andreas Bikfalvi; Katia Wehbe; Victor Kilarski; Guillaume Devès; Karine Gionnet; Richard Ortega; Sébastien Lavielle (MDPI AG, 2011)
PET (Positron Emission Tomography) allows imaging of the in vivo distribution of biochemical compounds labeled with a radioactive tracer, mainly 18F-FDG (2-deoxy-2-[18F] fluoro-D-glucose). 18F only allows a relatively poor spatial resolution (2-3 mm) which does not allow imaging of small tumors or specific small size tissues, e.g. vasculature. Unfortunately, angiogenesis is a key process in various physiologic and pathologic processes and is, for instance, involved in modern anticancer approaches. Thus ability to visualize angiogenesis could allow early diagnosis and help to monitor the response of cancer to specific chemotherapies. Therefore, indirect analytical techniques are required to assess the localization of fluorinated compounds at a micrometric scale. Multimodality imaging approaches could provide accurate information on the metabolic activity of the target tissue. In this article, PIGE method (Particle Induced Gamma-ray Emission) was used to determine fluorinated tracers by the nuclear reaction of 19F(p,p'γ)19F in tissues. The feasibility of this approach was assessed on polyfluorinated model glucose compounds and novel peptide-based tracer designed for angiogenesis imaging. Our results describe the first mapping of the biodistribution of fluorinated compounds in both vascularized normal tissue and tumor tissue.